Study on the Visual Experience of IP Image Design for Fruit-Based Foods - WU Qi-han; ZHOU Rui (Liang you shipin ke-ji)
China, as the world's largest producer and consumer of fruits, is transitioning to quality development. In the increasingly competitive food industry, innovative IP-based approaches can create unique cultural symbols for fruit-based foods. This study analyzes the current state of fruit food IP image design both domestically and internationally. Eye-tracking experiments were conducted to identify user visual attention focus. The Analytic Hierarchy Process (AHP) was adopted to construct an element framework for capturing the core elements of fruit food IP images. By solving attribute weights and clarifying user needs, qualitative and quantitative methods were combined to transform subjective concepts into measurable data. The visual experience of fruit food IP images was deeply explored through key attributes such as brand visual symbols, brand tone, and style evolution. Finally, innovative pathways for domestic fruit food IP image design were proposed.